Analisis Kelayakan Perencanaan Pengembangan Bisnis Hotel Sentosa di Kota Palembang - Michelle Usman; Yulizar Kasih (Universitas Multi Data Palembang, 2022)
Abstrak: This study aims to analyze the business feasibility of developing the Sentosa Hotel in Palembang City. The high level of competition and the impact of the Covid-19 pandemic had affected room sales performance 5 years ago. In 2020 sales performance began to improve, accompanied by increased demand for hotel rooms during the new normal, so Sentosa Hotel plans to develop its business. The development plan is focused on innovating Smart Hotel facilities, Tour Guides and collaborating with culinary restaurant businesses typical of the city of Palembang as souvenirs. Business feasibility analysis is carried out using 3 analytical methods, namely financial statement analysis, feasibility analysis, and business profit analysis. Based on the results of the analysis (PP, NPV, IRR, PI, ARR, BEP) obtained, it can be stated that the Sentosa Hotel business development plan is feasible to run. Abstract: